An integrated videoconferencing intervention for chronic pain and heavy drinking among patients in HIV-care: a proof-of-concept study. Issue 9 (1st September 2020) - Palfai, Tibor P.; Saitz, Richard; Kratzer, Maya P. L.; Taylor, Jessica L.; Otis, John D.; Bernstein, Judith A.
ABSTRACT: Chronic pain and heavy drinking are common comorbid conditions among people living with HIV/AIDS (PLWHA). An integrated approach to address these co-occurring conditions in a manner that facilitates treatment utilization would represent an important advance in HIV-care. This study examined the acceptability and feasibility of a tailored, videoconferencing intervention to reduce chronic pain and heavy drinking among PLWHA. Participants in HIV-care (n = 8) completed baseline assessments and an in-person intervention session followed by 6 videoconferencing sessions. Acceptability and feasibility were assessed with patient satisfaction ratings and interview responses 8 weeks following baseline along with videoconferencing use during the intervention period. Treatment satisfaction and comprehensibility ratings were high and supported by interview responses indicating the value of the intervention content, treatment alliance, and format. All participants successfully enabled videoconferencing on their own smartphones and completed a median number of 4.5 (out of 6) video-sessions. Changes in heavy drinking and pain provided additional support for the potential utility of this approach. Results suggest that this videoconferencing intervention is an acceptable and feasible method of addressing chronic pain and heavy drinking among PLWHA. Findings provide the basis for future work to examine the efficacy of this approach in a Stage 1b trial.